Distribution and Control of Herbicide-Resistant Italian Ryegrass [Lolium perenne L. ssp. multiflorum (Lam.) Husnot] in Winter Wheat (Triticum aestivum L.) in North Carolina - Jones, Eric A. L.; Taylor, Zachary R.; Everman, Wesley J. (Frontiers in Agronomy, 2021)
Italian Ryegrass is consistently ranked as one of the most problematic weeds of winter wheat in the Southeastern United States. To determine the distribution of resistant Italian ryegrass biotypes, seed was collected from locations throughout North Carolina and screened with diclofop, pinoxaden, mesosulfuron, and pyroxsulam. Results identified evidence of resistance to diclofop at all locations sampled throughout the state, resistance to ALS-inhibitors mesosulfuron or pyroxsulam in eleven to nineteen percent, and resistance to pinoxaden in five percent of sampled locations. Additionally, Italian ryegrass resistant to all herbicides tested were identified, eliminating POST herbicide application as an option for control. Adjusting tillage practices may be an option for sustainable weed management to maintain effective control and maximize crop yield. Companion studies were established in the Coastal Plain and Piedmont regions of North Carolina in 2013 and 2014 to evaluate the effect of tillage on Italian ryegrass efficacy with herbicides. Herbicide treatments consisted of pyroxasulfone PRE followed by No POST, mesosulfuron, or pinoxaden and POST only applications of mesosulfuron plus pyroxasulfone or pinoxaden plus pyroxasulfone. Treatments containing pinoxaden provided the greatest Italian ryegrass control, regardless of tillage system. The use of pyroxasulfone PRE controlled a higher percentage of Italian ryegrass in the Piedmont when compared to the Coastal Plain, which is believed to be due to multiple flushes during the growing season in the Coastal Plain. Herbicide treatment was still a significant factor in Italian ryegrass control, but Italian ryegrass seed head density was consistently lower in the no till system. Tillage may be stimulating germination, allowing greater control with PRE herbicides. An integrated system of herbicides and tillage will allow for greater yield and reduce selection pressure on POST herbicides.